Weighting of sensory cues reflect changing patterns of visual investment during ecological divergence in Heliconius butterflies (2024)
Integrating information across sensory modalities enables animals to orchestrate a wide range of complex behaviours. The relative importance placed on one sensory modality over another reflects the reliability of cues in a particular environment and corresponding differences in neural investment. As populations diverge across environmental gradients, the reliability of sensory cues may shift, favouring divergence in neural investment and the weight given to different sensory modalities. During their divergence across closed-forest and forest-edge habitats, closely related butterflies Heliconius cydno and Heliconius melpomene evolved distinct brain morphologies, with the former investing more in vision. Quantitative genetic analyses suggest that selection drove these changes, but their behavioural consequences remain uncertain. We hypothesized that divergent neural investment may alter sensory weighting. We trained individuals in an associative learning experiment using multimodal colour and odour cues. When positively rewarded stimuli were presented in conflict, i.e. pairing positively trained colour with negatively trained odour and vice versa, H. cydno favoured visual cues more strongly than H. melpomene. Hence, differences in sensory weighting may evolve early during divergence and are predicted by patterns of neural investment. These findings, alongside other examples, imply that differences in sensory weighting stem from divergent investment as adaptations to local sensory environments.